PENGARUH AUDIT MANAJEMEN SUMBER DAYA MANUSIA TERHADAP KINERJA KARYAWAN (STUDI EMPIRIS PADA HOTEL SWISS BELINN SURABAYA) - Awaluddin Awaluddin; Abdul Wahid Mahsuni; Affifudin Affifudin (e_Jurnal Ilmiah Riset Akuntansi, 2020)
This study aims to determine the effect of human resource management audits on employee performance. The population in this study is all employees Belinn Swiss Hotel in Surabaya. The sample used is a part of the beliss swiss hotel employees. The technique used in sampling is the probability sampling, the sample selected was 68 employess. Data was taken using the questionnaire method. The data analysis method used is simple regression analysis with the help of SPSS version 14 software (Product Statistics and Solution Services version 14). The test data used is the determination coefficient (R2), and partial hypothesis test (t). The results of the coefficient of determination, the adjusted R value is 58,9% while the remaining 41,1% is influenced by other variables not included in this study. Based on the results of the partial variables human resource management audit have an influence on employee performance with a significance value of (0,008).Keywords : human resource management audits, employee performance.